Usable but not entertaining e-learning materials - Abdul Mutalib, Ariffin (2008)
Interest in research related to experience-focused is growing.This paper looks into it by aiming to discover whether eLearning materials (eLMs) used in schools are easy to use and to investigate whether they are also entertaining the real users.Also it aims to deduce the results of the first two aims with previous works.All aims are achievable with the following steps. First, the eLMs are selected from those provided for use in schools.Then, a sample of fifteen real users is interviewed.Finally, results of both works are deduced.At the end, this study found that the eLMs are easy-to-use but are not entertaining.In addition we also hypothesize that users of eLM prefer to click less and watch more.